Competence in english and afrikaans in black post primary schools with special reference to the Northern Transvaal - Legodi, Manare Jeofrey (My University, 1992)
Refer to the document
Thesis (M.Ed.) -- University of the North, 1992
Keywords: Second languages; English teaching; Afrikaans teaching; Black schools; Language and education